An Analysis of the Determinants of Environmental, Social and Governance (ESG) Scores at the Firm level on Borsa İstanbul Companies - Sinan Aytekin; Nida Abdioğlu (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
Environmental, Social, and Governance (ESG) scores reflect how major corporations are evaluated based on ethical practices and sustainability efforts. This study aims to analyse the factors at the firm level that influence the ESG scores of 34 companies traded on Borsa Istanbul between 2018 and 2022. While the dependent variables are the ESG scores, the independent variables are financial leverage (LEV),c the logarithm of total assets (SIZE), return on invested capital (ROIC), return on capital employed (ROCE), market to book value (MB) ratio, and foreign net transactions/total volume (YS) ratio. The analyses are carried out individually, focusing on the three distinct aspects of corporate sustainability: environmental, social, and governance. This study employs fixed-effect panel data analysis utilizing the Driscoll and Kraay (1998) estimators. According to the results of the analyses, it is found that the variables LEV, ROCE, YS, and SIZE have positive impacts on ESG scores. Furthermore, the criteria that make up the ESG score are also examined separately. It is determined that the environmental criterion (ENV) is positively influenced by the variables LEV, ROCE, MB, and SIZE. The social criterion (SOC) is positively and significantly influenced by the variables LEV, ROCE, MB, and SIZE, while the variable ROIC has a negative effect. The governance criterion (GOV) is positively influenced by the variables ROCE, YS, and SIZE, while the variable MB has a negative impact on the criterion. The results of the analyses are in line with the legitimacy theory and agency theory.